Alignment of management control system to corporate competitive orientation: some empirical evidence in Malaysia - Foong, Soon Yau (Universiti Putra Malaysia Press, 2000)
With the rapidly changing and increasingly more competitive environment, the role of a management control system (MCS) in an organization in providing information feedback to management for monitoring the effectiveness and appropriateness of the organization's competitive strategy to achieve its goals is becoming more important. This study examines the extent of usage of various management control measures and the compatibility of these control measures with the competitive priorities or orientations of firms. A structured questionnaire was prepared and randomly sent to 250 organizations in the Klang Valley. A total of 93 usable responses were analyzed. The results show that organizations, generally, perceived competition based on product price, quality and service/promotion to be more intense than that based on product variety and innovation. Consistent to their perceived intensity of competition, their competitive priorities or orientations also stressed more highly on competition based on low price, high quality and service, with a much lower emphasis on wide product variety and product uniqueness. Except for an apparent pervasive high usage of the "budget vs. actual" financial control measure, there was a fairly balanced usage of accounting-based controls and modern management practices for monitoring, evaluating and controlling the organizational activities. Small enterprises tended to adopt less formal management control systems and had less extensive usage of the various control measures than the large firms. Evidence of a lack of proper alignment or incompatibilities in the usage of certain management control measures was indicated in this study. The implications of the findings are discussed.